Harun Farocki Forms of Intelligence - Alter, Nora M. 1962- (Columbia University Press, 2024)
Harun Farocki was one of the world's most celebrated experimental filmmakers at the time of his death in 2014. In a career spanning over fifty years, the German artist produced more than one hundred works, including political cinema, nonfiction film and video, and art installations, which have been exhibited globally. After his early politically engaged films in Super 8 and 16 mm, Farocki spent many years making independent films and commissions for German public television. In the last phase of his career, he transitioned to creating digital and multichannel installations. He also collaborated with the director Christian Petzold on a dozen films. In addition to his prolific media-making career, Farocki was an incisive critic and editor.This groundbreaking book is an incisive and comprehensive analysis of Farocki's oeuvre, shedding new light on his media experimentation and writings across platforms and venues. Nora M. Alter examines how Farocki's work investigates film and media images: their history, nature, manipulation, changing function, and strategic use. Focusing on interconnected ideas surrounding labor, critique, and war, she shows how his politically committed art is informed by pedagogical strategies that drive viewers to perceive how the media world they inhabit functions. Alter also argues that Farocki's career provides a lens on the history of avant-garde and experimental filmmaking amid shifts in materials and exhibition platforms. Tracing the transformations of Farocki's artistic practice and thought, this book offers new insight into the body of work of one of the most significant media makers of the late twentieth century